Nicotinic modulation of descending pain control circuitry. Issue 10 (October 2017) - Umana, Iboro C.; Daniele, Claire A.; Miller, Brooke A.; Abburi, Chandrika; Gallagher, Keith; Brown, Meghan A.; Mason, Peggy; McGehee, Daniel S.
Abstract : Abstract: Along with the well-known rewarding effects, activation of nicotinic acetylcholine receptors (nAChRs) can also relieve pain, and some nicotinic agonists have analgesic efficacy similar to opioids. A major target of analgesic drugs is the descending pain modulatory pathway, including the ventrolateral periaqueductal gray (vlPAG) and the rostral ventromedial medulla (RVM). Although activating nAChRs within this circuitry can be analgesic, little is known about the subunit composition and cellular effects of these receptors, particularly within the vlPAG. Using electrophysiology in brain slices from adult male rats, we examined nAChR effects on vlPAG neurons that project to the RVM. We found that 63% of PAG-RVM projection neurons expressed functional nAChRs, which were exclusively of the α7-subtype. Interestingly, the neurons that express α7 nAChRs were largely nonoverlapping with those expressing μ-opioid receptors (MOR). As nAChRs are excitatory and MORs are inhibitory, these data suggest distinct roles for these neuronal classes in pain modulation. Along with direct excitation, we also found that presynaptic nAChRs enhanced GABAergic release preferentially onto neurons that lacked α7 nAChRs. In addition, presynaptic nAChRs enhanced glutamatergic inputs onto all PAG-RVM projection neuron classes to a similar extent. In behavioral testing, both systemic and intra-vlPAG administration of the α7 nAChR-selective agonist, PHA-543, 613, was antinociceptive in the formalin assay. Furthermore, intra-vlPAG α7 antagonist pretreatment blocked PHA-543, 613-induced antinociception via either administration method. Systemic administration of submaximal doses of the α7 agonist and morphine produced additive antinociceptive effects. Together, our findings indicate that the vlPAG is a key site of action for α7 nAChR-mediated antinociception. Abstract : Supplemental Digital Content is Available in the Text.Nicotine has analgesic properties and some nicotinic drugs relieve pain as effectively as opioids. Previous studies have implicated the descending pain control pathway in nicotinic analgesia, but the underlying cellular mechanisms and receptor subtypes involved are largely unknown. Here we demonstrate that activation of α7 nicotinic receptors expressed by a subset of neurons in the periaqueductal grey can relieve tonic pain in an animal model. Understanding of the role of nicotinic receptors in pain control circuitry may lead to the development of more efficacious treatments for acute and chronic pain.